Co-designing climate adaptation strategies with women farmers: A manual for facilitators - Kori, Pooja; Puskur, Ranjitha; Mukhopadhyay, Prama; Chadha, Deepali (International Rice Research Institute, 2025)
Climate change poses significant challenges to livestock farmers and women farmers are often among the most vulnerable, especially in low and middle-income countries. With rising global temperatures and unpredictable weather patterns, livestock such as poultry and goats and the farmers who are dependent on them face increased adverse impacts on animal health, productivity, and overall farm livelihoods. This manual is designed to be a comprehensive resource for Trainers, specifically aimed at building the capacity of trainers who will, in turn, co-design relevant and context-specific solutions with women farmers on how to adapt to climate change, especially managing the impacts of heat stress and floods on their livestock and their livelihoods. The manual is structured to provide practical and feasible strategies that are context-specific and gender-responsive. It emphasizes participatory learning and co-creation of solutions, recognizing that these women livestock farmers possess valuable indigenous knowledge and practical insights that are vital for effective adaptation strategies.